Investigation of spatial and temporal variations of airborne Poaceae, Myrtaceae and Cupressaceae pollen and Alternaria spores in Sydney, Australia, 2017–2020 - Jetschni, Johanna; Al Kouba, Jane; Beggs, Paul J.; Jochner-Oette, Susanne (Aerobiologia, 2023)
There is a need for information on pollen exposure to assess allergy risk. Monitoring of aeroallergens in a city is usually limited to the use of a single trap for the whole area. While a single trap provides enough information on background pollen concentration for the area, varying pollen exposure across different urban environments, however, is not considered. In this study, we analysed aerobiological data of three pollen seasons (2017–2020) recorded with a volumetric pollen trap in Sydney, Australia. In order to assess spatial differences in pollen exposure across the city, we installed ten gravimetric traps recording pollen deposition for eight weeks during the summer of 2019/2020. We considered the influence of meteorological variables, land use, urbanisation and distance to the sea. Our results showed differences in pollen season characteristics across the three analysed seasons and correlations with meteorological parameters. Considering all years, we found for Poaceae and Alternaria the strongest positive correlation with mean temperature and for Myrtaceae and Cupressaceae with maximum temperature. Likewise, there were negative correlations with humidity (Myrtaceae, Cupressaceae, Alternaria ) and precipitation (Myrtaceae, Cupressaceae). Days with medically relevant pollen and spore concentrations varied between years and we recorded the highest amount in 2017/2018 for Poaceae and Alternaria and in 2019/2020 for Myrtaceae. In addition, we found spatial and temporal variations of pollen deposition. However, we did not detect significant correlations between pollen deposition and land use, which can be attributable to drought conditions prior to the sampling campaign and the temporal setting in the pollen season. This study highlights the importance of continuous volumetric aerobiological monitoring as well as the assessment of pollen exposure at several locations across a large urban area.